2015
DOI: 10.1088/1748-6041/10/3/034003
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically inspired cardiac scaffolds for tailoredin vivofunction and heart regeneration

Abstract: Tissue engineering is well suited for the treatment of cardiac disease due to the limited regenerative capacity of native cardiac tissue and the loss of function associated with endemic cardiac pathologies, such as myocardial infarction and congenital heart defects. However, the physiological complexity of the myocardium imposes extensive requirements on tissue therapies intended for these applications. In recent years, the field of cardiac tissue engineering has been characterized by great innovation and dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 112 publications
(149 reference statements)
2
46
0
1
Order By: Relevance
“…The in vivo examination of the CardioCel explants displayed extractable calcium levels comparable with the non-GA-crosslinked PhotoFix at 6 and 12 weeks (0.45 and 0.44 mg/mg tissue, respectively, 12 weeks), mirroring previous findings [9,12,20]. The highest extractable calcium levels were recorded for the 0.6% GA-fixed BP (means of 0.57 and 0.85 mg/mg tissue for XenoLogiX and PeriGuard, respectively, 12 weeks), but a longer study may be needed to uncover greater differences in calcification potential.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The in vivo examination of the CardioCel explants displayed extractable calcium levels comparable with the non-GA-crosslinked PhotoFix at 6 and 12 weeks (0.45 and 0.44 mg/mg tissue, respectively, 12 weeks), mirroring previous findings [9,12,20]. The highest extractable calcium levels were recorded for the 0.6% GA-fixed BP (means of 0.57 and 0.85 mg/mg tissue for XenoLogiX and PeriGuard, respectively, 12 weeks), but a longer study may be needed to uncover greater differences in calcification potential.…”
Section: Discussionsupporting
confidence: 84%
“…Stiffening of the extracellular matrix has also been shown previously for PeriGuard compared with the untreated tissue [15,19]. The lack of pliability of these materials may affect their performance in vivo, as stiffness can affect compliance, and the differences between the mechanical properties of aortic tissues and replacement materials can have unwanted haemodynamic effects leading to graft failure and can even affect the phenotype of cells binding to the bioscaffolds [20].…”
Section: Discussionmentioning
confidence: 77%
“…Formation of vascularized functional heart engineered tissue is the key determining factor in cardiac tissue engineering efficacy [Bursac, ]. It has been shown that interaction of cells with scaffold components through promoting the various signaling pathways can control the cells survival as well as stem cells proliferation, differentiation, and also formation of functional tissue [Kaiser and Coulombe, ]. Currently, the combination of several growth factors with scaffolds such as VEGF, b‐FGF, PDGFBB [Lin et al, ; Lisi et al, ; Matsuda et al, ] and IGF‐1 [Karam et al, ] is known to be an appropriate method for regulating the engineered tissue microenvironment and also for controlling the survival of the cells, and their differentiation.…”
Section: Cell Therapymentioning
confidence: 99%
“…Once the cells are injected or placed with a biomaterial matrix at the desired site in the heart, their fate needs to be tracked in vivo and this special section brings an original paper on in vivo tracking of angiogenic cells transplanted into rodent hearts [14]. Finally, the progress of in vivo pre-clinical studies with engineered cardiac tissues on biomaterial matrices are reviewed [15]. …”
mentioning
confidence: 99%